Extraosseous Extension of Aggressive Vertebral Hemangioma as a Potential Pitfall on 68Ga-PSMA PET/CT. (August 2017) - Probst, Stephan; Bladou, Franck; Abikhzer, Gad
Abstract : Abstract: A 74-year-old man with newly diagnosed prostate cancer underwent 68 Ga-PSMA PET/CT, which demonstrated intense uptake in and adjacent the L2 vertebral body. Subsequent MRI of the lumbar spine showed an aggressive L2 hemangioma with adjacent soft tissue extension. There was congruence of the intraosseous and extraosseous components of the hemangioma and the PSMA PET uptake. This is a rare but important potential pitfall in 68 Ga-PSMA PET/CT—a soft tissue lesion with intense tracer uptake related not to a nodal metastasis of prostate cancer but to extraosseous extension of an aggressive vertebral body hemangioma.